Studi Struktur Portal Baja Gedung Workshop Alat Berat Di Balai Wilayah Sungai Sumatera VI Tahap II Dengan Metode DFBK dan DKI - Bintang Muliardi Utamas; Suhendra Suhendra; Wari Dony (Universitas Batanghari Jambi, 2022)
Analysis of calculations and planning in steel structures there are 2 methods that are usually used, the methods are the method load factor and resistance design (DFBK) and the method allowable strength design (DKI). The method DFBK is a method that takes into account the working load multiplied by several safety factors so as to produce a factored load which is then used to calculate or plan a building, while the method DKI is a method that does not depend on the combined load factor in the calculation and in its planning, but uses stresses. permission which basically this method emphasizes the duration factor of the load that occurs on the structure. In this case study, the author aims to compare the method DFBK and so what distinguishes the two methods in a gable frame steel portal building. Both methods use the H-Beam 200.200.7.11 steel profile for the column, the I-WF 200.100.5.5.5.8 steel profile for the beam, and the CNP steel profile 100.50.5.7.5 with internal force analysis on the steel portal carried out with the program SAP 2000 with loading in accordance with SNI 1727-2020 and the results of the program SAP 2000 taken the largest moment, shear and axial for the calculation of the steel structure portal. Based on the results of the calculation of the deflection of the method DFBK of 2.4 cm, the bolts used were 10 bolts and the base plate thickness was 15 mm. While the method DKI of deflection is 2.1 cm, the bolts used are 6 bolts and the base plate thickness is 14 mm. Based on the results of the study and the conclusion that the deflection of the method DKI is smaller than the method DFBK, the bolt requirements and base plate thickness of the method DFBK are closer in terms of construction, so the method DFBK is safer and stronger.